Time Elapsed from Onset of Symptoms to Diagnosis of Gonorrhoea in Swedish Patients, 1999-2009 - Sharma, Arpana; Velicko, Inga; Kader, Manzur; Ahmad, Meraj (Asian Journal of Medical Sciences, 2013)
Background: Gonococcal infection remains an important public health problem worldwide. The incidence of reported gonorrhoea cases in Sweden raised by 32%, from 5.9 to 7.8 cases per 100,000 in 2001 to 2008.The aim of this study is to estimate the lag time or time elapsed between onset of symptoms and diagnosis of gonorrhoea, and to identify the factors associated with diagnostic delay in a sample of reported gonorrhoea cases in Sweden. Methods: A retrospective cohort study was conducted using all reported gonorrhoea cases at the Swedish Institute for Communicable Disease Control (SMI) from the time period 1999-2009. Total number of cases included in final analysis was 2161. Descriptive statistics, ANOVA, independent t-test and multiple linear regression analysis were applied for data analysis. Results: The mean lag time between onset of symptoms and diagnosis of gonorrhoea was 12.3 ± 18.8 days. There was a significant association of lag time with sex, region, type of clinics and type of specimen and year of diagnosis. In multivariate analysis with adjusted model, type of specimen was found to have independent effect on lag time and there was a significant interaction observed between region and sex indicating difference between sexes was due to difference in regions. Conclusion: The result of our study revealed a significant delay in establishing a diagnosis in Gonorrhoea patient sample in Sweden. The variables influencing this delay in diagnosis should be addressed to shorten the lag time leading to an early diagnosis and a proper treatment in our patients. However, more research needs to be carried out in this area to better understand the factors at work. DOI: http://dx.doi.org/10.3126/ajms.v5i1.8513 Asian Journal of Medical Science Vol.5(1) 2014 pp.20-28